Alcohol Injury Damages Intestinal Stem Cells. (10th March 2017) - Lu, Rong; Voigt, Robin M.; Zhang, Yongguo; Kato, Ikuko; Xia, Yinglin; Forsyth, Christopher B.; Keshavarzian, Ali; Sun, Jun
Abstract : Background: Alcohol consumption is associated with intestinal injury including intestinal leakiness and the risk of developing progressive gastrointestinal cancer. Alcoholics have disruption of intestinal barrier dysfunction that persists weeks after stopping alcohol intake, and this occurs in spite of the fact that intestinal epithelial cells turn over every 3 to 5 days. The renewal and functional regulation of the intestinal epithelium largely relies on intestinal stem cells (ISCs). Chronic inflammation and tissue damage in the intestine can injure stem cells including accumulation of mutations that may result in ISC dysfunction and transformation. ISCs are a key element in intestinal function and pathology; however, very little is known about the effects of alcohol on ISCs. We hypothesize that dysregulation of ISCs is one mechanism by which alcohol induces long‐lasting intestinal damage. Methods: In Vivo: Small intestinal samples from alcohol‐ and control‐fed mice were assessed for ISC markers (Lgr5 and Bmi1) and the changes of the β ‐catenin signaling using immunofluorescent microscopy, Western blotting, and RT‐PCR. Ex Vivo: Organoids were generated from small intestine tissue and subsequently exposed to alcohol and analyzed for ISC markers, β ‐catenin signaling. Results: Chronic alcohol consumption significantly decreased the expression of stem cell markers, Bmi1 in the small intestine of the alcohol‐fed mice and also resulted in dysregulation of the β ‐catenin signaling—an essential regulator of its target gene Lgr5 and ISC function. Exposure of small intestine‐derived organoids to 0.2% alcohol significantly reduced the growth of the organoids, including budding, and total surface area of the organoid cultures. Alcohol also significantly decreased the expression of Lgr5, p‐ β ‐catenin (ser552), and Bmi1 in the organoid model. Conclusions: Both chronic alcohol feeding and acute exposure of alcohol resulted in ISC dysregulation which might be one mechanism for alcohol‐induced long‐lasting intestinal damage. Abstract : Our studies on intestinal stem cells (ISC) in the mouse model and organoids provide unique and fundamental insights into alcohol‐induced injury on the intestine: alcohol disrupts ISC homeostasis, in part, through the β‐catenin pathway. Investigating how the β‐catenin pathway is altered by alcohol may provide critical insight into alcohol‐induced effects on ISC function and pathology. Studies on alcohol‐induced injury in ISCs possibly shed light on the association between alcohol consumption and intestinal cancer, as well as alcohol‐induced gut leakiness and inflammation.